THE ROLE OF MASS MEDIA IN SHAPENING PUBLIC PERCEPTION OF ISLAMIC EDUCATION POLICY - Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; Wasehudin; Aceng Hasani; Abdul Muin (Cakrawala Pedagogik, 2026)
This study aims to analyze the role of mass media in shaping public perceptions of Islamic education policies in Indonesia. Mass media plays a strategic role as a means of disseminating information and shaping public opinion through framing, issue selection, and news presentation. The research method used is a qualitative approach with library research supported by content analysis of various media reports related to Islamic education policies. Data were collected from journal articles, online news, and relevant policy documents, then analyzed descriptively and analytically. The results indicate that mass media plays a significant role in shaping public perceptions through the construction of social reality influenced by editorial perspectives, vested interests, and media ideology. Positive reporting tends to increase public trust in Islamic education policies, while negative reporting can foster critical perceptions and even public resistance. Furthermore, the public's level of media literacy also influences how the public understands and interprets the information conveyed. Therefore, an active role is needed for the government, educational institutions, and the public to respond critically to information to create an objective and constructive perception of Islamic education policies.